Обчислювальний підхід до дослідження темплант/мономерних комплексів меламін імпринтованих полімерів - Музика, К. М.; Рожицький, М. М. (ХНУРЭ, 2012)
In this work a computational approach to investigation of template/monomer complex in imprinted polymers enable us to select monomers interacting strongly with the melamine as target analyte. The molecular modeling and performing thermodynamic computations were carried out with the help of a patented protocol developed at Cranfield University, UK. The binding energies shows the acrylamido-2-methyl-1-propanesulfonic acid (AMPSA) is the best binding monomer for melamine followed by itaconic acid and F22 ethylene glycol methacrylate phosphate (EGMP). Розробка та дослідження сенсорних властивостей нових наноматеріалів, які можуть суттєво покращити аналітичні властивості сенсорів, а саме підвищити їх селективність та чутливість, є актуальним завданням, вирішення якого лежить на перетині різних наук.
Keywords: наноелектроніка; штучні рецептори; Molecular imprint polymer; binding energy